Preoperative intensity-modulated chemoradiotherapy with simultaneous integrated boost in rectal cancer - But-Hadžić, Jasna (Radiology and oncology (Ljubljana), 2021)
. We conducted a phase II study to investigate the feasibility and safety of preoperative radiochemo-therapy experimental fractionation, using intensity-modulated radiation therapy with simultaneous integrated boost (IMRT SIB) to shorten the overall treatment time without dose escalation in intermediate/locally advanced rectal cancer with the aim to improving treatment outcome.Patients and methods. A total of 51 patients with operable stage II–III rectal carcinoma were included between January 2014 and January 2015. Fifty patients completed preoperative IMRT treatment with an elective dose of 41.8 Gy and simultaneously delivered 46.2 Gy to T2/T3 and 48.4 Gy to T4 tumour in 22 fractions, with concomitant capecit-abine (825 mg/m2/12 h, including at weekends). Median follow-up was 70 months (range 11–80 m).Results. Forty-seven patients completed treatment per protocol. Acute toxicity occurred in 2 (4%) patients. R0 resec-tion was achieved in all but 1 and pathologic complete response (pCR) in 12 (25.5%) patients who had 5-year overall survival (OS), disease-free survival (DFS) and local control (LC) of 91.7%, 100% and 100%, respectively. The intention-to-treat analysis showed that the type of surgery significantly moderated OS and DFS, while total downstaging and pN were predictive for DFS only. For treatment per protocol 5-year OS, DFS and LC were 80.9% (95% confidence interval CI 69.7–92.1), 77.1% (95% CI 65.1–89.1) and 95.2% (95% CI 88.7–100), respectively. The proportion of patients with severe late (CTCAE G ? 3) gastrointestinal, urinary and sexual toxicity was 15%, 2% and 8% respectively, with one reported secondary carcinoma.
Keywords: acute toxicity; IMRT; preoperative radiochemotherapy; rectal cancer; simultaneous integrated boost